2021
DOI: 10.3332/ecancer.2021.1313
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of completion of cancer directed treatment: an experience from a rural cancer centre, Sangrur, Punjab state, India

Abstract: In low and middle-income countries, access to cancer diagnosis and treatment is suboptimal. Further, compliance to cancer treatment is a major issue due to various reasons including financial barriers, lack of family support and fear of treatment. This article discusses the determinants of treatment completion in cancer patients of a government-run hospital, in a rural part of Punjab in India. The Sangrur hospital-based cancer registry data for the year 2018 have been used. We have registered 2,969 cancer case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…2) was breast (15 cases; 33.3%) followed by head and neck (H&N) cancer (10 cases; 22.2%), gynecological cancer (5 cases; 11.1%), prostate cancer (4 cases; 8.9%), esophagus cancer (2 cases; 4.4%), and other sites (9 cases; 20.0%) which are also in the top leading sites in males and females in HBCR. 22 The most common site for second malignancy (►Fig. 3) was the gastrointestinal tract (GI tract) (14 cases; 31.1%) followed by gynecological cancer (8 cases; 17.8%), H&N (7 cases 15.6%), hematological (3 cases; 6.7%), soft tissue sarcoma (STS) (2 cases; 4.4%), breast (1 case; 2.2%), and other sites (10 cases; 22.2%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) was breast (15 cases; 33.3%) followed by head and neck (H&N) cancer (10 cases; 22.2%), gynecological cancer (5 cases; 11.1%), prostate cancer (4 cases; 8.9%), esophagus cancer (2 cases; 4.4%), and other sites (9 cases; 20.0%) which are also in the top leading sites in males and females in HBCR. 22 The most common site for second malignancy (►Fig. 3) was the gastrointestinal tract (GI tract) (14 cases; 31.1%) followed by gynecological cancer (8 cases; 17.8%), H&N (7 cases 15.6%), hematological (3 cases; 6.7%), soft tissue sarcoma (STS) (2 cases; 4.4%), breast (1 case; 2.2%), and other sites (10 cases; 22.2%).…”
Section: Resultsmentioning
confidence: 99%
“…2 ) was breast (15 cases; 33.3%) followed by head and neck (H&N) cancer (10 cases; 22.2%), gynecological cancer (5 cases; 11.1%), prostate cancer (4 cases; 8.9%), esophagus cancer (2 cases; 4.4%), and other sites (9 cases; 20.0%) which are also in the top leading sites in males and females in HBCR. 22 …”
Section: Resultsmentioning
confidence: 99%
“…High use of pesticides, presence of toxic material also in sub-soil water, leaching of uranium from rocks, and presence of thermal power plants based on coal are thought to the reasons for the high incidence of cancer in the state of Punjab, India. The work of Aggarwal et al [29] on the pattern of cancer incidence in the Malwa region of the Punjab, was published in March 2015, demonstrated breast cancer to be the leading cancer (35%) among all cancer cases, (most common), and 4% cases were of gall bladder cancer (fifth highest cases), whereas in a recent study published November 2021 by Budukh et al [30] on cancer cases reported in the Homi Bhaba cancer institute, Sangrur reported GB cancer being the 3rd most common cancer (7.9%). Here we can observe that the proportion of gall bladder cancer cases among all cancer cases significantly increased from 4% to almost 7.9% in the north Indian region of Punjab over a period of few years.…”
Section: Discussionmentioning
confidence: 98%
“…According to data from various hospital-based cancer registries in India, 50%–60% of cancer patients did not complete cancer-directed treatment. [ 28 29 ] However, we would like to emphasize and acknowledge the limitation that, based on the study results, the disease was most likely metastatic, and treatment for such patients is lifelong. Clinically, the completion of treatment is not relevant; however, from the epidemiological perspective, these findings would be useful for developing public health strategies to improve treatment completion.…”
Section: Discussionmentioning
confidence: 99%